2014
DOI: 10.1063/1.4904713
|View full text |Cite
|
Sign up to set email alerts
|

Localized heating of electrons in ionization zones: Going beyond the Penning-Thornton paradigm in magnetron sputtering

Abstract: The fundamental question of how energy is supplied to a magnetron discharge is commonly answered by the Penning-Thornton paradigm invoking secondary electrons. Recently, Huo and coworkers (Plasma Sources Sci. Technol. 22, 045005 (2013)) used a global discharge model to show that electron heating in the electric field of the magnetic presheath is dominant over heating by secondary electrons. In this contribution, this concept is applied locally taking into account the electric potential structure of ionization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 34 publications
(40 reference statements)
1
37
1
Order By: Relevance
“…39. The measurements of potential distribution together with obtained electric field, space charge, and electron energization distributions presented in this work therefore provide a greater insight into the dynamics, sustainability, and mechanism of localized electron heating 46 in moving ionization zones. The choice of investigating the ionization zones in DCMS offers a great advantage as opposed to the investigating zones in HiPIMS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39. The measurements of potential distribution together with obtained electric field, space charge, and electron energization distributions presented in this work therefore provide a greater insight into the dynamics, sustainability, and mechanism of localized electron heating 46 in moving ionization zones. The choice of investigating the ionization zones in DCMS offers a great advantage as opposed to the investigating zones in HiPIMS.…”
Section: Discussionmentioning
confidence: 99%
“…In that sense, the here-described electron energization in a double layer is Ohmic heating. Following the prior work, 46 Ohmic heating appears to be highly localized involving electrons going to a higher potential, where the potential difference exceeds the ionization energy. Ohmic heating as viewed in this work thus includes two mechanisms: a collisionless mechanism where electrons gain energy from the potential jump (i.e., electric field of the double layer), and a collisional heating mechanism in which electrons gain energy via collisions when moving from lower to higher equipotential lines.…”
Section: -12mentioning
confidence: 99%
See 1 more Smart Citation
“…presented a model that is based on the localised generation of secondary electrons [15]. The configuration of the electric field along the target's racetrack was first discussed by Brenning et al [16] and later modified by Anders et al [17,18]. In the latter publication it is argued that for a closed racetrack, the potential needs to be reproduced when returning to the same location.…”
Section: Introductionmentioning
confidence: 99%
“…The predictive power of equation 1 is, however, limited since any change of the plasma is affecting all parameters simultaneously. A more recent modification of equation 1 has been proposed by Anders [13] on the basis of Ohmic heating in the magnetic presheath of the HiPIMS plasma, as proposed by Huo et al [14], who found a very good agreement between measured currents and a global model of the plasma. The connection between current and voltage is usually expressed in the form of a power law with the current I proportional to the voltage V as I ∝ V n .…”
Section: Introductionmentioning
confidence: 99%